Design of a sand filter for recycling ablution water from IIUM Masjid - Mamun, Abdullah Al (s.n, 2012)
A significant amount of water is required daily for IIUM Masjid. Unfortunately, the used water is discharged directly t the drain without any treatment to recycle and reuse. The ablution water is not that much polluted and can be recycled and reused for general cleaning and landscaping purpose. On the other hand, treatment and reuse of commercial greywater would be too expensive in the contexts of Malaysia climate. Therefore, the ablution water discharged from IIUM Masjid was characterized for potential reuse in the campus. A cost effective, low maintenance treatment system need to be designed and fabricated to collect, treat and reuse ablution water. Details about the quantity and quality of the ablution water from IIUM Masjid and how to design the filter are presented in this paper